Pemberian Orientasi Mempengaruhi Tingkat Kecemasan Orang Tua Menghadapi Hospitalisasi pada Anak Usia Sekolah - I Gusti Ayu Putu Satya Laksmi; I Wayan Erik Febriana; Desak Made Ari Dwi Jayanti (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
The impact of hospitalization on children who are hospitalized can cause an anxiety reaction forparents. Some parental anxiety responses can be minimized by providing a complete orientationto parents regarding the process of hospitalization and treatment of children. This study aims todetermine the relationship between orientation and the level of anxiety of parents facinghospitalization in school-age children. This research method uses a descriptive correlation designwith a cross sectional approach. The sampling method used is probability sampling withpurposive sampling technique. The number of samples in this study were 37 respondents. Thedata collection tool used is a questionnaire. The data analysis technique used the Spearman Rank(rho) statistical test. The results of data analysis showed the value of r = 0.512 and p-value = 0.001which means that there is a significant relationship between orientation and the level of anxietyof parents facing hospitalization in school-age children. Giving room orientation to new patientscan be said to be good and the level of anxiety experienced by parents is a mild level of anxiety. Inconnection with the results of this study, the role of nurses is needed in providing a completeorientation to parents whose children are hospitalized so as to reduce the level of parentalanxiety.